Pengembangan Kriteria Seleksi pada Pisang (Musa sp.) Berdasarkan Analisis Lintas - Desta Wirnas; Sobir Sobir; Memen Surahman (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
This research was aimed to develop selection criteria based on correlation and path coefficient analysis.  The experiment was carried out at CETROFS (Center for Tropical Fruit Studies) field station of Bogor Agricultural University, Tajur.  The result showed that plant height, pseudostem diameter, number of leaves, weeks to harvest,  finger number per plant, and mean of  finger weight were positively correlated with bunch weight. Pseudostem diameter,  number of leaves, finger number per plant have strong direct effect on bunch weight,  with path coefficient 0.321, 0.264, 0.297, and 0.722, subsequently.  However, the plant height showed strong indirect effect on bunch weight  through  pseudostem diameter. These characters  are useful as a selection criteria for developing new variety of banana  with higher bunch weight   Key words: path coefficient, selection criteria, banana